Ravnikar-Zupanov pozabljeni prevod Pentatevha - Skralovnik, Samo (Edinost in dialog, 2023)
The paper answers the key questions regarding Ravnikar-Zupan's translation of the Pentateuch: why it remained in the manuscript, when it was translated and who is its translator. The translation is first placed in the wider socio-cultural situation by presenting the attitude of the Catholic Church towards the translation of the Bible in the first half of the 19th century and shedding light on the functioning of state and church censorship. By evaluating the correspondence between the members of Zois's circle who participated in the creation of the translation, the questions of authorship and the year of creation of the translation are addressed. In contrast to the current practice, which addresses the translation as Ravnikar's, it is shown that it is more correct to speak of Ravnikar-Zupan's translation, since it is clear from the letters between Kopitar, Zupan and Zois that Ravnikar did not translated the Pentateuch himself. The letters also show that the entire translation of the Pentateuch was completed in November 1812. In the last part of the article, by analysing a few lines of the first chapter of the Genesis in both versions of the manuscript, it is shown that the R1 manuscript depends on Japelj-Kumerdej's translation solutions, which mostly fully or partially summarizes it, and also on Dalmatin's translations solutions. It is indicated that in the case of manuscript R1, the translators did not start from scratch, but rather, similar to their contemporaries, adapted the biblical text of already existing translations. The same applies to manuscript R2, but to a lesser extent and with a greater dependence on Dalmatin, which also exhibits specific linguistic characteristics evident in Ravnikar's printed books.
Keywords: Bible; Biblia; jansenism; janzenizem; jezikovna analiza; Kopitar, Jernej; linguistic analysis; Pentatevh; prevajanje Svetega pisma; Ravnikar, Matevž; Slomšek, Anton Martin; Sveto pismo; translation of the Bible; Wolf, Anton Alojzij; zupan, jakob